2014
DOI: 10.3109/09637486.2014.971226
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and quantification ofγ-oryzanol in grains of 16 Korean rice varieties

Abstract: γ-Oryzanol, a mixture of ferulic acid esters of triterpene alcohols and sterols, is a nutritionally important group of rice secondary metabolites. A library of 27 γ-oryzanol was assembled from existing data and used to assist identification and quantification of γ-oryzanol isolated from 16 Korean rice varieties (11 white and 5 pigmented). γ-Oryzanol was analyzed with liquid chromatography with diode array detection and electrospray ionization mass spectrometry. Nineteen different γ-oryzanol were observed and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The average c-oryzanol contents in black-purple, green, red and brown rice varieties were 54.2 ± 6.2, 47.3 ± 4.4, 44.6 ± 6.1 and 43.3 ± 4.1 mg OE/100 g dried weight, respectively. The c-oryzanol contents of the regular brown rice varieties observed in this study were consistent with those reported previously (Miller and Engel 2006;Kim et al 2015). A statistically significant difference in average c-oryzanol content was found between black-purple rice varieties and other rice varieties (p \ 0.05).…”
Section: Resultssupporting
confidence: 92%
“…The average c-oryzanol contents in black-purple, green, red and brown rice varieties were 54.2 ± 6.2, 47.3 ± 4.4, 44.6 ± 6.1 and 43.3 ± 4.1 mg OE/100 g dried weight, respectively. The c-oryzanol contents of the regular brown rice varieties observed in this study were consistent with those reported previously (Miller and Engel 2006;Kim et al 2015). A statistically significant difference in average c-oryzanol content was found between black-purple rice varieties and other rice varieties (p \ 0.05).…”
Section: Resultssupporting
confidence: 92%
“…As other reports have already demonstrated (Heineman et al, 2008;Huang & Ng, 2011;Kim et al, 2015;Miller & Engel, 2006;Roohinejad et al, 2011), this experiment also showed very wide and significant variations in gOZ and GABA concentrations in BN, BG, and PG among cultivars (Figures 3 and 4). Only for GABA concentration in PN, no significant variation was detected.…”
Section: Goz and Gaba Concentrations In Brown Rice And Polished Rice supporting
confidence: 84%
“…γ-oryzanol is a mix of triterpene alcohol and sterol ferulates with lipid-lowering actions by the inhibition of HMG-CoA reductase and the reduction of intestinal cholesterol absorption [ 183 ]. To date in Korea at least 16 varieties of rice bran oil, containing different percentages of γ-oryzanol (26.7 to 61.6 mg/100 g), have been identified [ 184 ].…”
Section: Other Nutraceuticals With Mixed Mechanisms Of Actionmentioning
confidence: 99%